Timelines of science - Challoner, Jack (DK Publishing, 2013)
"Follow the story of science year by year with [an] ... illustrated timeline with ... explanations of key scientific theories and concepts; identify the influential thinkers behind revolutionary breakthroughs and discover how they changed the world; trace the development of landmark innovations such as the measurement of time, computers, and mobile communication; see major advances and achievements in their broader context"--Zadní s. obálky
Nad názvem: DK Smithsonian
"The ultimate visual guide to the discoveries that shaped the world"--Z obálky
Terminologický slovník
Obsahuje rejstřík
Keywords: dějiny vědy; dějiny přírodních věd; dějiny objevů a vynálezů; history of science; history of natural sciences; history of discoveries and inventions; chronologické přehledy; chronological surveys